A rare case of twins with bilateral congenital ptosis – a case report - Abdul Rashid, Aneesa; Devaraj, Navin Kumar; Abdul Manap, Abdul Hadi; Mohd Abdullah, Azlindarita Aisyah; Mohamad, Fadzilah (Consortium of Senior Medical Faculties, 2020)
Cases of congenital ptosis are rare, let alone bilateral and occurring in twins. There are many diagnostic dilemmas, often needing genetic testing and advanced imaging such as magnetic resonance imaging. This case report will look at the case of a twin with this interesting feature who are presented to a primary care clinic. It will center around how the diagnosis of congenital fibrosis of extraocular muscles was reached and what management options are available for this twin.